EVALUASI TATA KELOLA KEAMANAN SISTEM INFORMASI MENGGUNAKAN FRAMEWORK COBIT 5 PADA PT. TSABITA CAKE - Azifa Habiba (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
This research aims to evaluate the maturity level of information technology governance (IT) in the application of information system services at PT. Tsabita Cake. The method used is a mixed method of quantitative and qualitative using questionnaires, interviews, and document studies. The focus of this research is on the DSS 05 domain. The results obtained from this study are needed as an evaluation and input for improvement of the information system governance of PT. TSABITA CAKE in the future. The results showed the maturity level of IT governance in the Information System services of PT. TSABITA CAKE is currently at a capability of 75% or equivalent to 2.90 with the status largely achieved and at level 2. Therefore, information system security needs to be improved to support the performance of PT. TSABITA CAKE in order to reach level 3 requires a recommendation for gradual improvement of the attribute process from level 1 to level 3. To improve IT governance, it is recommended that institutions prepare competent human resources, as well as document every activity of evaluation, direction, and monitoring in information system management.